Relay selection algorithm based on selfish behavior analysis in ultra-dense D2D - Yijun WANG; Youxu ZHANG; Dakun LIU; Guifen CHEN (Tongxin xuebao)
In ultra-dense D2D communication, the current relay selection schemes mainly assume that the relay device has the initiative to participate in data forwarding, but some rational relay devices may delay or refuse to forward due to their own considerations, thus affecting the user experience.From the perspective of selfish behavior of relay devices, a method to identify selfish relay devices in D2D communication was proposed, and then an ultra-dense D2D relay selection algorithm based on selfish behavior analysis was proposed.Firstly, three relay identification attribute factors, namely joint interest degree (JID), forwarding history ratio (FHR) and relay physical state (RPS) were defined, and their weights were calculated by triangular fuzzy function to identify relay devices with selfish behavior.Secondly, based on the TOPSIS (technique for order of preference by similarity to ideal solution) method, the final relay equipment selection scheme relay was realized.Simulation results show that the proposed algorithm can identify selfish relay devices more effectively in D2D communication.Compared with other relay selection algorithms, the proposed algorithm has made significant progress in the aspects of D2D communication forwarding success rate, system average throughput and average time delay.